Addressing Childhood Obesity in Urban Brazil: A Public Health Strategy for Prevention and Intervention - Oliveira, Maria S. (Generasi Sains Indonesia, 2024)
Childhood obesity is a growing public health concern in urban Brazil, driven by socio-economic disparities, unhealthy dietary habits, and sedentary behaviors. This study aims to examine the key determinants of childhood obesity and assess the effectiveness of current public health interventions. A cross-sectional quantitative design was used to collect data from 1,000 children aged 5-14 in major urban areas, including São Paulo and Rio de Janeiro. The results reveal that children from lower socio-economic backgrounds are at higher risk of obesity due to limited access to healthy food and recreational spaces. Screen time was positively correlated with BMI, while physical activity was negatively correlated, indicating the importance of reducing sedentary behaviors and promoting active lifestyles. School-based physical activity programs were found to be effective in reducing obesity rates, though gaps in program reach and equity remain. The study concludes that a comprehensive, equity-focused public health strategy is essential for addressing childhood obesity in urban Brazil, with a particular emphasis on expanding access to physical activity programs and addressing socio-economic barriers to healthy living.